Tunneling assisted p-contact free GaN-InGaN green light-emitting diodes - Jamshad Bashir; Muhammad Usman; Shazma Ali; Laraib Mustafa (Journal of Information Display)
The effects of bottom tunnel junction (TJ) on optoelectronic characteristics of green light-emitting diodes are analyzed numerically. Our proposed LED has enhanced internal quantum efficiency (IQE), radiative recombination rate, and carrier concentration in comparison to reference conventional LED. The IQE increases by 17%, droop is reduced by 28%, and emission intensity is nearly twice as high as than reference design. The improved optical properties of the proposed structure are due to excellent carrier confinement and altered spontaneous polarization in the vicinity of the active region by TJ.